THE RISE OF ANTIMICROBIAL RESISTANCE IN 2023: A GLOBAL AND INDIAN HEALTHCARE PERSPECTIVE"- A SHORT COMMUNICATION - C., Madhavi (International Journal of Research -GRANTHAALAYAH, 2024)
Antimicrobial resistance (AMR) has reached alarming levels globally, and India is at the forefront of this crisis. In 2023, Indian hospitals are witnessing an increase in multidrug-resistant bacterial infections. This short communication highlights key examples of AMR from Indian hospitals, exploring common resistant bacterial strains, underlying causes, and strategies for mitigation. Data from tertiary care hospitals, national reports, and the Indian Network for Surveillance of Antimicrobial Resistance (INSAR) are reviewed to understand the depth of the issue and potential solutions.